Where the power lies: multiple stakeholder politics over natural resources: a participatory methods guide - Sithole, B. (Center for International Forestry Research, 2002)
This manual is a participatory methods guide (1) to assist those involved with multiple stakeholder situations or groups to appreciate and acknowledge the relevance and impact of micro-politics on stakeholder relations and resultant cooperative behaviour in these groups; (2) to provide a simple and systematic approach or framework to gather and analyse data on micro-politics among multiple stakeholders; (3) to highlight and offer practical suggestions for dealing with some of the methodological issues that influence gathering data on politics and relations among stakeholders; (4) to suggest some methods drawn from participatory methodologies like Participatory Rural Appraisal (PRA) and Participatory Action Research (PAR) that can be used in data gathering. Data from two sites in Zimbabwe are presented at various stages and the annexes to illustrate how this framework can be applied and show the type of data that can be gathered.